A Soli Deo Gloria Református Diákszövetség Kecskeméten - RIGÓ, Róbert (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
The Soli Deo Gloria Reformed Student Association in Kecskemét. At the beginning of my study, I show that in Kecskemét there was a very inten-sive Reformed association life in gender-, age-group-based and thematically or-ganized groups in the first half of the 20th century, the aim of the growing youth organizations being to strengthen religious education and to raise Hungarian na-tional awareness; thus, their attention turned towards the young people living on farms. Local Reformed youth organizations became more and more wide-spread, with similar organizations functioning in Budapest and Debrecen. After some preparations, the Soli Deo Gloria Reformed Student Union began operat-ing in the boys’ grammar school in the 1932/33 school year, and by the end of the decade, nearly half of the students had participated in its work. During the war, a student movement was also organized among girls in the girls’ grammar school and in the teacher training college. In my study, I present the diverse ac-tivities of the local organization of SDG in detail, which, besides self-education and community development, also tried to find solutions to the social problems of the local society.